UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI SD 096753 DESA PERLANAAN DUSUN IV KABUPATEN SIMALUNGUN SUMATERA UTARA - Amalia Hikmayanti Tambunan; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2021)
Islamic Religious Education wants students to have a strong foundation of faith and piety to Allah Subhanahu Wa'Taala. Faith is a belief in the heart with full confidence which is then actualized into good deeds in accordance with Islamic religious teachings so as to produce achievements called piety. The teacher's efforts in improving student learning achievement are of course very diverse, apart from the many efforts made by the teacher there are also obstacles experienced by educators as the learning process or the teacher's process progresses in improving student learning achievement, from these obstacles it also leads the teacher to seek solution of any obstacles experienced by the teacher. That solution is then used as a benchmark for teachers in facing any obstacles in the process of improving student learning achievement. The research method used in this preparation is to use a qualitative approach where the approach is in the form of a systematic description of the matter being discussed.